CONECTIVIDADE ESTRUTURAL E FUNCIONAL DA PAISAGEM DA FLORESTA NACIONAL DE PIRAÍ DO SUL E ENTORNO, PARANÁ, BRASIL - Barros, Karina Ferreira de (2015)
The focus of this analysis was the mantainance of connectivity in landscape as a fundamental principle for biodiversity conservation, where ecological flows are considered highly relevant to planning aimed at environmental conservation. The combination between the geography spatial analysis and functional analysis of ecology allows the understanding of landscape connectivity from the interaction between the physical arrangement of the landscape (structural connectivity) and the response of organisms to these physical structures (functional connectivity). In Piraí do Sul National Forest, a 153ha unit of conservation of sustainable use within the Atlantic forest biome, the calculation of structural metrics revealed the predominance of a little permeable matrix modified by agriculture, forestry, livestock and roads. Predomine small patches with 75% of the fragments lesser than 3,2ha. The few larger patches are aggregated. There is a high proportion of edge (13.3% of the total area), with 70% of the patches entirely subject to edge effects. The spatial disposition of the patches imply in low supply of habitat, because although over 53% of the patches were in the vicinity of another fragment at a distance of up to 20 m, its neighbors in that search radius are very small. The low level of connectivity (6.3%) also is a strong indicator of the degree of fragmentation. Only 4.4% of the total area of the landscape consists on corridors, mostlly determined by the hydrographic network. The functional analysis reveals that the perception of landscape connectivity is variable, and for generalists animal species, the profile of size and arrangement of patches does not compromise the offset among the elements of the landscape. Specialized animal species, however, perceive a scenario of fragmentation highly compromising. For the plant species, the structural characteristics of the patches constitute secondary aspects to the landscape perception. Fragmentation of the landscape must be brought to discussion on the Managing Council of Piraí do Sul National Forest and should be treated within the management plan. This should incorporate appropriate criteria to the confrontation of the ecological problem represented by the proven framework of landscape fragmentation. To do so, are discussed specific contributions of the connectivity analysis.